2012
DOI: 10.1093/ntr/nts236
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Phase and Depressive Symptoms Differences in Physiological Response to Nicotine Following Acute Smoking Abstinence

Abstract: introduction: Accumulating evidence has linked depressive symptoms and sex hormones to risk for relapse; however, the specific mechanisms involved in these associations remain unknown. This randomized crossover study assessed physiological response to nicotine by menstrual phase in female smokers with and without depressive symptoms following acute smoking abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…These data are similar to our recent observations, of women without depressive symptoms, revealing that the follicular phase, as compared with the luteal phase, was associated with a more pronounced physiological response to nicotine nasal spray during short-term smoking abstinence (e.g. greater diastolic blood pressure and heart rate, and higher maximum concentrations of nicotine) [59]. Similarly, Schiller et al [60•] observed that lower PE ratios were associated with increased smoking.…”
Section: Sex Hormonessupporting
confidence: 91%
“…These data are similar to our recent observations, of women without depressive symptoms, revealing that the follicular phase, as compared with the luteal phase, was associated with a more pronounced physiological response to nicotine nasal spray during short-term smoking abstinence (e.g. greater diastolic blood pressure and heart rate, and higher maximum concentrations of nicotine) [59]. Similarly, Schiller et al [60•] observed that lower PE ratios were associated with increased smoking.…”
Section: Sex Hormonessupporting
confidence: 91%
“…We highlight research methodology of the S. Allen et al [45]•• study because the controlled cross-over design has several strengths, including limiting confounds, multimodal assessments, between- and within-subject data, and information on both follicular and luteal phases within the same participant. As such, several publications have resulted from using this strong research approach [4649, 26, 45, 50, 51]. …”
Section: Acute Smoking Abstinence Studiesmentioning
confidence: 99%
“…Studies have looked at links between depression and smoking (Weinberger & McKee, 2011; Wewers, et al, 2012), hormonal fluctuations and smoking (Allen, et al, 2008; Lynch, & Sofuoflu, 2010; Sofuoglu, Mouratidis, & Mooney, 2010) and hormonal fluctuations and depression (Allen, et al, 1999; Allen, et al, 2012; & Harvey, et al, 2009), but none have addressed the potential synergistic effects of sex hormones (as measured by the proxy menstrual phase) and depressive symptoms during smoking cessation. Given that the vast majority of premenopausal women relapse within the first few days of a quit attempt (Allen, et al, 2008), the present study was designed to examine the risk factors for smoking relapse within the first four days of abstinence.…”
Section: Introductionmentioning
confidence: 99%